A descriptive study on student’s satisfaction towards services provided in Universiti Malaysia Kelantan - Ravikumar S/O Parumal, . (2012)
This study determines the level of satisfaction among the University Malaysia Kelantan UMK) students towards the facilities provided such as the sport facilities, accommodation, bus transportation and classroom environments out of all the universities facilities. The study was based on a survey that is administered involving 100 students as respondents. By using the descriptive analysis the level of satisfaction among the students towards the facilities provided by UMK are examined. The findings show that the level of satisfaction among students is at acceptable level. Most of students are satisfied with the facilities provided by the university. The findings of this study will help UMK improve their quality of services provided to the students.